Occupational noise‐induced hearing loss in auto part factory workers in welding units in Thailand. Issue 1 (24th January 2017) - Sriopas, Apiradee; Chapman, Robert S.; Sutammasa, Saravudh; Siriwong, Wattasit
Abstract : Objectives: Most workers in auto part factories in Thailand are usually exposed to excessive noise in their workplace. This study aimed to assess the level of occupational noise‐induced hearing loss and investigate risk factors causing hearing loss in auto part factory workers in the welding units in Thailand. Methods: This was a cross‐sectional study. One hundred eighty subjects were recruited from 356 workers in the welding unit of three factories. Sixty eligible subjects in each factory were selected by systemic random sampling. The subjects were interviewed using a face‐to‐face questionnaire. Noise exposure levels and audiograms were measured by a noise dosimeter and an audiometer, respectively. Results: The findings confirmed that noise exposure levels of 86‐90 dB (A) and exceeding 90 dB (A) significantly increased the risk of hearing loss in either ear. A noise exposure level exceeding 90 dB (A) significantly increased the prevalence of hearing loss in both ears. Regarding, a 10‐pack‐year smoking history increased the prevalence of hearing loss in either ear or both ears. In addition, subjects with employment duration exceeding 10 years significantly developed hearing loss in either ear. Conclusions: Th engineering control or personal control by wearing hearing protection device should be used to decrease noise exposure levels lower than 85 dB (A) for 8 h. Moreover, if the exposure level reaches 85 dB (A) for 8 h, the employer needs to implement a hearing conservation program in the workplace.